Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00284-016-1079-8
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolate and Desulfo-glucosinolate Metabolism by a Selection of Human Gut Bacteria

Abstract: Glucosinolate (GSL) hydrolysis is mediated by the enzyme myrosinase which together with specifier proteins can give rise to isothiocyanates (ITCs), thiocyanates, and nitriles (NITs) in cruciferous plants. However, little is known about the metabolism of GSLs by the human gut flora. The aim of the work was to investigate the metabolic fates of sinigrin (SNG), glucotropaeolin (GTP), gluconasturtiin (GNT), and their corresponding desulfo-GSLs (DS-GSLs). Three human gut bacterial strains, Enterococcus casseliflavu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…The authors could demonstrate myrosinase activity with intact cells but not with cell-free protein extracts. Subsequent studies [23,24] with L. agilis R16 showed similar results with sinigrin except that allylnitrile was also a product. This study was expanded to include glucotropaeolin, gluconasturtiin, glucoraphanin, glucoerucin, and glucoiberin.…”
Section: Isothiocyanate Productionmentioning
confidence: 64%
See 3 more Smart Citations
“…The authors could demonstrate myrosinase activity with intact cells but not with cell-free protein extracts. Subsequent studies [23,24] with L. agilis R16 showed similar results with sinigrin except that allylnitrile was also a product. This study was expanded to include glucotropaeolin, gluconasturtiin, glucoraphanin, glucoerucin, and glucoiberin.…”
Section: Isothiocyanate Productionmentioning
confidence: 64%
“…Glucoerucin-and glucotropaoelin-like sinigrin were converted to ITCs and nitriles. [23,24] It was not possible to demonstrate myrosinase activity with cell-free protein extracts. Further studies were carried out with two bacterial strains Enterococcus casseliflavus CP1 and Escherichia coli VL8 that originated from human fecal material.…”
Section: Isothiocyanate Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, a three-day withdrawal from the broccoli diet decreased GRP hydrolysis ex vivo, suggesting that frequent broccoli ingestion may be essential for this improved microbial GRP hydrolysis. Recent studies have shown that desulfoglucosinolates can be substrates for beta hydrolase, resulting in formation of nitriles [40]. It will be interesting to see if there are bacterial N-sulfatase enzymes that are able to generate desulfoglucosinolates and whether these, by forming inactive nitriles and not reactive isothiocyanates, can protect the bacterium from glucosinolate toxicity.…”
Section: Discussionmentioning
confidence: 99%